THE RISK OF DEGENERATIVE DISEASES BASED ON ENERGY CONSUMPTION AND EXERCISE HABITS - Ni Made Yuni Gumala; Hertog Nursanyoto; I Wayan Ambartana (Jurnal Riset Kesehatan, 2023)
Obesity triggers the risk of degenerative diseases. An unhealthy diet and insufficient physical activity have been contributing to the rapid increase in obesity prevalence. This study aims at determining the differences in the risk of degenerative diseases based on energy consumption and exercise habits of City Disaster Management Board/DMB members, especially in Denpasar City. This research is an observational study, targeting all members of Denpasar DMB as a population. Samples were taken purposively with a total of 126 people. The risk difference was tested using chi-square, and the estimated risk of degenerative diseases was analyzed using the Mantel-Haentzel odds ratio. The risk of degenerative diseases based on energy consumption shows a significant risk only in the group of people who did not have exercise habits (Q-suare=4.53; p=0.03), with an estimated risk that is also significant (OR=2.48; 95% CI= 1.07 - 5.74). The estimated risk results indicated that exercise habit is a potential confounding variable in the risk of degenerative diseases based on energy consumption. Lowering energy consumption is not effective enough to prevent the increase of degenerative disease risk, and prevention of new risks of degenerative diseases must include regular exercise.